The application of social networks in the travel planning of Generation Z - Sudarević Tomislav; Kostić Dunja; Jevtić Jelena (Marketing (Beograd. 1991))
Digital media has led to significant changes in the behavior of young people. A significant contribution to the further development of the tourism sector is particularly noteworthy. These digital media facilitate the process of making decisions about choosing and planning trips and are an inevitable means of searching, collecting and marketing information and content for members of Generation Z. Social networks significantly simplified the way of communication between users and thus became an easily accessible source of data. Photos, videos, comments as well as reviews or ratings of other travelers are the most frequently searched content formats. Visual representations and recommendations give potential travelers a better idea of what kind of experience they can expect when visiting a particular destination. The essence of recommendations is that they come from other travelers, and this type of content rarely causes suspicion among users, considering that they represent the sharing of their own subjective experience. In order to understand how social media and the content shared on them influence travel planning among Generation Z, research was conducted using the Pearson correlation test on the territory of the Republic of Serbia. The results of the research confirmed the connection between how photos, videos, comments and reviews on social networks have a significant relationship and influence on the search for the necessary information about tourist services through social media. Taking into account the obtained research results, it is possible to adapt and create better content on social networks that will encourage tourists who are members of Generation Z to make a decision. The results of the conducted research can act as an incentive for further analysis of the behavior of members of Generation Z when planning trips with the use of social media, especially if future research is conducted on respondents outside the territory of the Republic of Serbia.